Application of Dilute Hydrogen Peroxide Gas Technology for Continuous Room Decontamination of Multidrug-Resistant Organisms: Negative Results from A Preliminary Experimental Study. (4th October 2017) - Rutala, William A; Kanamori, Hajime; Gergen, Maria; Sickbert-Bennett, Emily; Anderson, Deverick; Sexton, Daniel; Weber, David J
Abstract: Background: Healthcare room environmental surfaces can be frequently and continuously contaminated with multidrug-resistant organisms (MDROs) that can persist in the environment for a prolonged time. Here, we used a dilute hydrogen peroxide (DHP) gas system for continuous room decontamination and experimentally examined the germicidal efficacy of the new technology against MDROs. Methods: DHP units were installed in ceilings of a model room and the hallway in front of the room. We tested three test organisms; methicillin-resistant staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and MDR- Acinetobacter baumannii . An estimated 100–500 CFU for each test organism was inoculated and spread separately on each Formica sheet then exposed to DHP gas released into the room air. Triplicate samples were collected at times 0, 1, 3, 5, 6, 7, 24, and 48 hours. Following incubation, the colony forming units (CFU) of the test organisms on each Rodac plate were counted. Two separate experimental trials were performed for all time points. Statistical significance between intervention and control groups at each time point was determined by the Wilcoxon test, and P < 0.05 was considered significant. Results: There were no statistical differences in survival between DHP intervention and control groups except data at very few time points for each organism (i.e., for MRSA in Figure 1, P = 0.0063 at 24 hours; for VRE in Figure 2, P = 0.0163 at 1 hour, P = 0.0163 at 3 hours; for MDR- Acinetobacter in in Figure 3, P = 0.0369 at 24 hours). The survival curves between both groups for each organism intersected at around 24 hours. The DHP units maintained a germicidal concentration (<0.3ppm for all runs) that was inadequate, despite attempts to control factors that could interfere with the hydrogen peroxide gas concentration. Conclusion: Our preliminary study using DHP demonstrated inactivity against MDROs on room surfaces, likely because we were unable to generate a sufficient germicidal level under our test conditions with the particular DHP units. Additional technologic modifications would be required to maintain stable and effective DHP level for continuous room decontamination in patient rooms. Disclosures: D. Sexton, Centers for Disease Control and Prevention: Grant Investigator, Grant recipient. Centers for Disease Control and Prevention Foundation: Grant Investigator, Grant recipient. UpToDate: Collaborator, Royalty Recipient. D. J. Weber, PDI: Consultant, Consulting fee.